Real time measurements of elongation by a reverse transcriptase using surface plasmon resonance. - Buckle, M (1996)
A rapid direct assay for polymerase-induced elongation along a given template is an obligate requirement for understanding the processivity of polymerization and the mode of action of drugs and inhibitors on this process. Surface plasmon resonance can be used to follow the association and the dissociation rates of a given reverse transcriptase on DNA.RNA and DNA.DNA hybrids immobilized on a biotin-streptavidin surface. The addition of nucleotides complementary to the template strand produces an increase in the local mass, as deduced from an increase in the measured signal, due to elongation of the primer strand that allows an estimation of both the extent and rate of the polymerization process. The terminator drug 3'-deoxy-3'-azidothymidine triphosphate completely abolishes the increase in signal as would be expected from an inhibition of elongation. This technique provides a sensitive assay for the affinities of different polymerases for specific templates and for the effects of terminators of the elongation process.